Flood risk zoning due to climate change under RCP 8.5 scenario using hydrologic model SWAT in Gis (Azarshahr basin) - Mohammadreza Goodarzi; Atiyeh Fatehifar (تحقیقات کاربردی علوم جغرافیایی)
In the present time, with the increase of industrial activities and the neglected environmental issues, the effects of climate change have become more evident and poses this phenomenon as a global difficult. Increasing the probability of occurrence of extreme climatic events such as flood and increasing the frequency and intensity of the effects of climate change. The northwest of the country is one of the most vulnerable areas of the country due to its semi-arid and mountainous climates and high rainfall variability. Therefore, zoning due to climate change is essential. Therefore, in this study, in order to investigate the risk of flood in the Azarshahr basin, due to climate change, using the CanESM2 general circulation model under RCP8.5 scenarios negativity according to the assessment report fifth IPCC, rainfall and temperature variables were down scaling by Statistical down scaling model (SDSM). Then,with hydrological model SWAT the daily runoff, the basin map and the lines of the canals are achieved. The results of the evaluation of the SDSM model with a coefficient of determination and Nash-Sutcliff 0.95 on average represent the good performance of the model in the down scaling of large scale data. The results show an increase of 0.23 ° C and 4.53% rainfall and maximum discharge. The basin is zoned with the combination of the maximum mean discharge map, the coefficient and distance from the river with the AHP approach. Due to the zoning they are 41.55% of the area of the basin, at very low and low risk, 27.23% at average risk and 31.2% at high and very high risk. Also, with the final map, it became clear that the mid-basin had a high risk due to its prerequisite conditions and that it needed to carry out managerial actions.